Standardisation and validation of a triage system in a private hospital group in the United Arab Emirates - Dippenaar, Enrico (Division of Emergency Medicine, 2017)
Introduction: Upon inspection and evaluation of the Mediclinic Middle East emergency centres in the United Arab Emirates, inconsistencies related to triage were found. Of note, it was found that the use of various international triage systems within and between the emergency centres may have caused potentially harmful patient conditions. The aim of this thesis was to study the reliability and validity of existing triage systems within Mediclinic Middle East, and then to use these systems as a starting point to design, standardise and validate a single, locally appropriate triage system. This single triage system should be able to accurately and safely assign triage priority to adults and children within all of Mediclinic Middle East emergency centres. Methods: A System Development Life Cycle process intended for business and healthcare service improvement was expanded upon through an action research design. Quantitative and qualitative components were used in a five-part study that was conducted by pursuing the iterative activities set by an action research approach to establish the following: the emergency centre patient demographic and application of triage, the reliability and validity of the existing triage systems, a determination of the most appropriate triage system for use in this local environment and development of a best-fit novel triage system, establishment of validation criteria for the novel triage system, and determination of reliability and validity of the novel triage system within Mediclinic Middle East emergency centres. Results: Low-acuity illness profiles predominated the patient demographic; high acuity cases were substantially smaller in number. The emergency centres used a combination of existing international triage systems; this was found to be inappropriate for this environment. Poor reliability and validity performance of the existing triage systems led to the development of a novel, four-level triage system. This novel triage system incorporates early warning scores through vital sign parameters, and clinical descriptors. The novel triage system proved to be substantially more reliable and valid than the existing triage systems within the Mediclinic Middle East emergency centres. Conclusion: Through an initial systems analysis, it became clear that the Mediclinic Middle East emergency centres blindly implemented an array of international triage systems. Using an action research approach, a novel triage system that is both reliable and valid within this local environment was developed. The triage system is fit to be implemented throughout all the Mediclinic Middle East emergency centres and may be transposed to similar emergency centre settings elsewhere.